Clinical Profile of Patients with Heart Failure in Eastern Part of Nepal: a Hospital based study - Monib, Abdul Khaliq; Dhungana, Sahadeb Prasad; Nepal, Rajesh; Ghimire, Rinku (Journal of Nobel Medical College, 2019)
Background: There is limited information on the clinical profile of patients with heart failure from the Nepalese population. Materials and Methods: This is a descriptive cross-sectional study on 120 consecutive patients with New York Heart Association class II or IV symptoms of heart failure admitted from June 2018 to January 2019 at Nobel Medical College Teaching hospital, Biratnagar, Nepal. Results: Mean age was 52.2 ± 20.6 years. The male and female ratio was 0.71. Ischemic cardiomyopathy, rheumatic heart disease, dilated cardiomyopathy, acute coronary syndrome, hypertensive heart disease, and peripartum cardiomyopathy were common etiologies constituting 22.5%, 19.1%,13.3%, 9.1%, 8.3 %, 5% of cases respectively. Among co-morbid conditions, anemia (91.6%),hypertension (31.6%), coronary artery disease (29.1%), diabetes (20.8%) and chronic kidney disease (11.6%) were common. Among various drugs used, 66.6% patients were prescribed diuretics, 60% mineral corticoid receptor blockers, 33.3% angiotensin-converting enzymeinhibitors, 33.3% beta-blockers, 29.1% digoxin and 8.3% angiotensin receptor blockers. Echocardiography revealed LV systolic and diastolic dysfunction in 75% and 25% respectively, mitral regurgitation in 52.5%, right ventricular dysfunction in 10.8 % and pulmonary artery hypertension in 66.6%. Conclusion: Appropriate use of evidence-based therapies, careful attention to the diagnosis and management of specific co-morbidities in patients with HF may help to improve outcomes.